Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1186/s13027-021-00381-4
|View full text |Cite
|
Sign up to set email alerts
|

Association between colorectal cancer and Fusobacterium nucleatum and Bacteroides fragilis bacteria in Iranian patients: a preliminary study

Abstract: Background and aim Recent studies have proposed that commensal bacteria might be involved in the development and progression of gastrointestinal disorders such as colorectal cancer (CRC). Therefore, in this study, the relative abundance of Fusobacterium nucleatum, Bacteroides fragilis, Streptococcus bovis/gallolyticus, and Enteropathogenic Escherichia coli (EPEC) in CRC tissues, and their association with clinicopathologic characteristics of CRC was investigated in Iranian patients. Moreover, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 31 publications
2
29
0
Order By: Relevance
“…Enrichment of F. nucleatum has been identified in CRC patients and is associated with worse outcomes [ 28 , 29 ]. CRC tissues have a higher abundance of F. nucleatum and B. fragilis bacteria than normal tissues in Iranian patients, and it has been recommended that the role of CRC-associated bacteria in CRC be further investigated in vivo and in vitro [ 30 ]. As it can be detected in both CRC tissues and feces of patients with CRC [ 31 ], F. nucleatum could serve as a potential marker for diagnosing patients with CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Enrichment of F. nucleatum has been identified in CRC patients and is associated with worse outcomes [ 28 , 29 ]. CRC tissues have a higher abundance of F. nucleatum and B. fragilis bacteria than normal tissues in Iranian patients, and it has been recommended that the role of CRC-associated bacteria in CRC be further investigated in vivo and in vitro [ 30 ]. As it can be detected in both CRC tissues and feces of patients with CRC [ 31 ], F. nucleatum could serve as a potential marker for diagnosing patients with CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Shariati et al (2021) showed a significantly higher abundance of B. fragilis and F. nucleatum in fresh frozen biopsies of colorectal lesions of Iranian CRC patients compared to adjacent normal mucosal tissues. However, they could not detect such a relation for S. gallolyticus and EPEC [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Their findings could potentially be explained through ethnic differences in susceptibility to colorectal colonization of S. gallolyticus or geographical differences in S. gallolyticus distribution. Furthermore, these discrepancies may also be related to application of diverse specimens (like fresh frozen tissues, FFPE and stool) and different detection methods (such as qPCR, pyrosequencing, Fluorescence In Situ Hybridization) used for detection of S. gallolyticus [ 1 , 5 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations